Sosialisasi Tanaman Indigofera Sebagai Pakan Tambahan Ternak Ruminansia Desa Sukamandi Hulu - Adrianus Bari; Andriansyah Kusuma; Alvin Geovani Sitompul; Anggi Pramana; Daniel Daniel (Yayasan Literasi Sains Indonesia, 2022)
This community service program is carried out to introduce the community to the benefits of the Indigofera sp. As an additional feed for ruminants. Feed is the most important factor in livestock business. The problem that is often faced in livestock business is the provision of forage feed ingredients. The purpose of this community service program is to find out the potential of indigofera forage plants as animal feed in Sukamandi Hulu Village, Pagar Merbau District, Deli Serdang Regency, North Sumatra. Indigofera sp plants have very good nutrient content, including crude protein (PK) of 27.9%, crude fiber (SK) of 15.25% and quite high mineral content, namely calcium (Ca) 0.22% and phosphorus 0 .18%. The results obtained are that Indigofera sp. has a high nutritional content that can be used as additional forage feed which is very useful for growth than ruminant livestock. Indigofera sp. Can also survive in relatively dry and extreme land. The conclusion that can be drawn from this program is that Indigofera sp. Potential to be developed as animal feed in Sukamandi Hulu Village.